Investigating Business Opportunities of Griya Event Space in Bali to Strengthen the Household Economy - Desak Made Febri Purnama Sari; Ida Ayu Iswari Pidada; Ida Ayu Oka Martini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Hindu communities have shifted ceremonial practices from household settings to organized venues known as Griya in contemporary times. This study aims to examine the business opportunities of Griya Event Spaces as a potential solution to household economic challenges in Tampaksiring, Gianyar. This study employed a qualitative research design with a descriptive approach to gain an in-depth understanding of business opportunities. Data were collected through observation, interviews, and documentation, employing a qualitative descriptive approach. The findings reveal that griya event spaces demonstrate a strong customer-oriented approach, as reflected in the quality of services provided. Nevertheless, its marketing practices remain inadequate. The management primarily adopts a passive strategy, relying on customers to initiate contact and attend ceremonies without actively engaging in promotional activities or efforts to attract visitors. Consequently, the involvement of the local community, particularly those acting as pengayah or supporting business actors, has not been optimized. Furthermore, the study identifies limitations in the proportional recording of employees and the management of human resources. The absence of a formal customer service system further reflects the reliance on conventional practices, characterized by a passive approach and a lack of proactive promotional strategies.